Diabetic muscle infarction: two cases: one with recurrent and bilateral lesions and one with usual unilateral involvement. (2013)
Diabetic muscle infarction is a rare complication of diabetes. We describe 2 cases of diabetic muscle infarction, each one of them with a particular form of clinical presentation: recurrence, bilateral engagement, and unilateral compromise. Both cases had history of poorly controlled diabetes mellitus and diabetic nephropathy. The diagnosis was based on clinical, imaging, and anatomopathological features. The treatment was with a close control of diabetes mellitus, analgesics, short-term immobilization, and physical therapy.